Applying Portfolio Management to Implement Ecosystem-Based Fishery Management (EBFM). (3rd May 2016) - Jin, Di; DePiper, Geret; Hoagland, Porter
Abstract: Portfolio management has been suggested as a tool to help implement ecosystem-based fisheries management. The portfolio approach involves the application of financial portfolio theory to multispecies fishery management to account for species interdependencies, uncertainty, and sustainability constraints. By considering covariance among species, this approach allows economic risks and returns to be calculated across varying combinations of stock sizes. Trade-offs between expected aggregate returns and portfolio risk can thus be assessed. We develop a procedure for constructing portfolio models to help implement ecosystem-based fisheries management in the northeastern United States, using harvest data from the National Marine Fisheries Service. Extending the work of Sanchirico et al. (2008), we propose a measure of excessive risk taking, which may be used by managers to monitor signals of nonoptimal harvests. In addition, we conduct portfolio assessments of historical commercial fishing performance at different accounting stances: the large marine ecosystem, the New England region, and the community (fishing ports). We show that portfolio analysis could inform management at each level. Results of the study suggest that excessive risk taking is associated with overfishing, and risk management is therefore important for ensuring sustainability. Received June 28, 2015; accepted January 14, 2016